Challenges and Solutions for Improved Oral Health: Examples from Motivational Interviewing Trials - Jamieson, L.M. (JDR Clin Trans Res, 2019)
Irrespective of country, socially disadvantaged children experience greater levels of preventable dental disease than their more socially advantaged peers. Motivational interviewing (MI) is recognized as a potential intervention tool for reducing prevalence of child dental disease. The challenges of implementing MI in 4 trials involving socially vulnerable children are highlighted in this commentary, with some potential solutions offered.